Functional Roles of Starch Binding Domains and Surface Binding Sites in Enzymes Involved in Starch Biosynthesis - Wilkens, Casper; Svensson, Birte; Møller, Marie Sofie (Frontiers in Plant Science, 2018)
Biosynthesis of starch is catalysed by a cascade of enzymes. The activity of a large number of these enzymes depends on interaction with polymeric substrates via carbohydrate binding sites, which are situated outside of the catalytic site and its immediate surroundings including the substrate-binding crevice. Such secondary binding sites can belong to distinct starch binding domains (SBDs), classified as carbohydrate binding modules (CBMs), or be surface binding sites (SBSs) exposed on the surface of catalytic domains. Currently in the Carbohydrate-Active enZYmes (CAZy) database SBDs are found in 13 CBM families. Four of these families; CBM20, CBM45, CBM48, and CBM53 are represented in enzymes involved in starch biosynthesis, namely starch synthases, branching enzymes, isoamylases, glucan, water dikinases, and -glucan phosphatases. A critical role of the SBD in activity has not been demonstrated for all of these enzymes. Among the well-characterised SBDs important for starch biosynthesis are three CBM53s of Arabidopsis thaliana starch synthase III, which have modest affinity. SBSs, which are overall less widespread than SBDs, have been reported in some branching enzymes, isoamylases, synthases, phosphatases and phosphorylases active in starch biosynthesis. SBSs appear to exert roles similar to CBMs. SBSs, however, have also been shown to modulate specificity for example by discriminating the length of chains transferred by branching enzymes. Notably, the difference in rate of occurrence between SBDs and SBSs may be due to lack of awareness of SBSs. Thus, SBSs are not recognised at the protein sequence level and the function only a few SBSs in enzymes from starch biosynthesis have been validated by using site-directed mutagenesis guided by crystal structures of carbohydrate complexes. The glucan phosphatase Like SEX4 2 from A. thaliana has two SBSs with weak affinity for β-cyclodextrin, amylose and amylopectin, which were indicated by mutational analysis to be more important than the active site for initial substrate recognition. The present review provides an update on occurrence of functional SBDs and SBSs in enzymes involved in starch biosynthesis.